2022
DOI: 10.3389/fnagi.2021.807907
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and Intra-Hemispheric Age-Related Remodeling in Visuo-Spatial Working Memory

Abstract: Electroencephalography (EEG) studies investigating visuo-spatial working memory (vWM) in aging typically adopt an event-related potential (ERP) analysis approach that has shed light on the age-related changes during item retention and retrieval. However, this approach does not fully enable a detailed description of the time course of the neural dynamics related to aging. The most frequent age-related changes in brain activity have been described by two influential models of neurocognitive aging, the Hemispheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 86 publications
(148 reference statements)
2
2
0
Order By: Relevance
“…Thus, the results of the present study align with studies showing negative relationships between increased inter-hemispheric dedifferentiation and cognitive functioning in older adults (Knights et al, 2021; Koen and Rugg, 2019; Morcom and Jonson, 2015). Finally, differences between HCR and LCR groups in inter-hemispheric asymmetries for P300 but not for N200 are consistent with a recent ERP study (Tagliabue et al, 2022), suggesting that reduced inter-hemispheric asymmetrical activity associated with ageing does not uniformly affect all stages of information processing.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, the results of the present study align with studies showing negative relationships between increased inter-hemispheric dedifferentiation and cognitive functioning in older adults (Knights et al, 2021; Koen and Rugg, 2019; Morcom and Jonson, 2015). Finally, differences between HCR and LCR groups in inter-hemispheric asymmetries for P300 but not for N200 are consistent with a recent ERP study (Tagliabue et al, 2022), suggesting that reduced inter-hemispheric asymmetrical activity associated with ageing does not uniformly affect all stages of information processing.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, the results of the present study align with studies showing negative relationships between increased inter-hemispheric dedifferentiation and cognitive functioning in older adults (Knights et al, 2021;Koen and Rugg, 2019;Morcom and Johnson, 2015). Finally, differences between HCR and LCR groups in inter-hemispheric asymmetries for P300 but not for N200 are consistent with a recent ERP study (Tagliabue et al, 2022), suggesting that reduced inter-hemispheric asymmetrical activity associated with ageing does not uniformly affect all stages of information processing.…”
Section: Tablesupporting
confidence: 92%
“…In this regard, functional magnetic resonance imaging (fMRI) studies revealed a posterior to anterior shift of brain activity (e.g., Davis et al, 2008;Morcom and Henson, 2018) and reduced inter-hemispheric asymmetries (e.g., Cabeza, 2002;Roe et al, 2020) in older adults during the performance of cognitive tasks. Accordingly, research using ERPs reported that ageing was associated with diminished parietal ERP amplitudes in addition to increased frontal activity (Daffner et al, 2011;Friedman et al, 1997;Saliasi et al, 2013;van Dinteren et al, 2014) as well as reduced inter-hemispheric asymmetries (Angel et al, 2011;Learmonth et al, 2017;Tagliabue et al, 2022) during the performance of cognitive tasks. The posterior to anterior shift of activity was related to deployment of frontal mechanisms to compensate processing deficits in posterior areas, whereas the loss of brain asymmetries was taken as a sign of compensatory activity by the contralateral hemisphere as well as dysfunctional processes characterised by loss of cortical specificity (for a review, see McDonough et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…A typical cognitive impairment that follows the discourse of aging is reduced performance in working memory (WM) tasks (Salthouse et al, 1991 ; Park et al, 2002 ). This is generally observed as a lower accuracy in older adults (OAs) compared to young adults (YAs) with increasing sets of objects that need to be remembered (Jost et al, 2011 ; Sander et al, 2011 ; Tagliabue et al, 2019 , 2022 ). Because of the set size manipulation, most studies have concluded that there is a reduction in the amount of object representations that OAs can hold in WM in comparison to YAs (Jost et al, 2011 ; Schwarzkopp et al, 2016 ; Tagliabue et al, 2020 but see Oberauer and Kliegl, 2010 ); this interpretation falls in line with the viewpoint of WM capacity as a fixed-slot model (Luck and Vogel, 1997 ; Cowan, 2001 ; see Adam et al, 2017 for more recent results), in which an individual's WM is set at a fixed number of representations, regardless of the content of the representations (Awh et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%